ANTI-METASTATIC MECHANISM AND EFFICACY OF BROMELAIN - Dhanashree Sumeet Chakraborty (International Journal of Ayurveda and Pharma Research, 2015)
Bromelain, an enzyme from the pineapple plant has varied pharmacological activities, out of which it shows specific anticancer activity and now is gaining attention regarding this aspect. Medicinal qualities of bromelain include antiedematous; anti-inflammatory, anti-thrombotic, fibrinolytic, immunogenicity and it is used in the treatment of thrombosis and thrombophlebitis, diarrhea, debridement of burns etc. This article reviews the mechanism and efficacy of bromelain in fighting against tumor cells, inspite of it being a natural drug with enzymatic background. Bromelain shows antimetastatic efficacy and inhibits platelet aggregation, growth, and invasiveness of tumor cells. Its effectiveness and safety in cancer treatment has to be considered due to its Selective cytotoxicity. Bromelain being a plant extract, contains various components such as proteinases, peroxidises, phosphatises, protease inhibitors and organically bound calcium. These components might contribute to the variations of bromelains pharmacological activities. The main aim of this article is to focus the safety and efficacy of this drug in cancer treatment and comparing it with other chemotherapeutic agents.